Функціональний стан вазопресинергічної системи гіпоталамуса внаслідок дії переривчастої гіпоксичної гіпоксії - Шаменко, Вадим Олександрович; Шаменко В. А.; Shamenko V. O. (Запорізький державний медичний університет, 2020)
У дисертації наведене теоретичне обґрунтування і експериментальне вирішення актуальної наукової задачі, яка полягає у встановленні механізмів участі вазопресинергічної системи гіпоталамуса в нейроендокринній відповіді мозку на багатоденну переривчасту дію гіпобаричної гіпоксичної гіпоксії (ГГ) та особливостей відновлення морфофункціонального стану вазопресинергічних нейронів у постгіпоксичний період. На підставі кількісного імунофлуоресцентного дослідження серійних зрізів гіпоталамуса було показано, що ГГ призводила до гіпертрофії нейронів задньолатерального крупноклітинного суб'ядра ПВЯ(злкПВЯ), накопичення у цитоплазмі РНК, підвищення концентрації вазопресину у тілах нейронів та їх аксонах. ГГ підвищувала імунореактивність до білків cFos, HIF-1α і HIF-3α в злкПВЯ. У постгіпоксичний період у нейронах злкПВЯ зберігались основні показники вазопресин-синтезувальноїі нейросекреторної активності. Встановлено високу реактивність медіального дрібноклітинного суб'ядра ПВЯ (мдПВЯ) на ГГ у вигляді гіпертрофії нейронів, зростання концентрації РНК, збільшення імунореактивності до вазопресину зі зростанням і його сумарного вмісту у тілах та аксонах нейронів. Внаслідок ГГ в мдПВЯ зростала імунореактивність до білків cFos, HIF-1α і HIF-3α зі зростанням їх вмісту в структурі. Проте у постгіпоксичний період у мдПВЯ зменшувались імунореактивність до вазопресину і його вміст. У СОЯ ГГ викликали розвиток дистрофічних змін у нейроцитах і органелах зі зниженням концентрації РНК у нейронах, зменшенням імунореактивності до білків HIF-1α,HIF-3α, cFos і до вазопресину, з частковим відновлюванням функції у постгіпоксичний період. В диссертации приведено теоретическое обоснование и экспериментальное решение актуальной научной задачи, которая заключается в установлении механизмов участия вазопрессинергической системы гипоталамуса в нейроэндокринном ответе мозга на многодневное действие прерывистой гипобарической гипоксической гипоксии(ГГ) и особенностей восстановления морфофункционального состояния вазопрессинергических нейронов в постгипоксический период. На основании количественного иммунофлюоресцентного анализа серийных срезов гипоталамуса было показано, что ГГ приводила к гипертрофии нейронов заднелатерального крупноклеточного субъядра ПВЯ (злкПВЯ), накоплению в цитоплазме РНК, повышению концентрации вазопрессина в телах нейронов и аксонах, росту суммарного содержания вазопрессина в ПВЯ. В злкПВЯ ГГ повышала иммунореактивность к белкам cFos, HIF-1α и HIF-3α. В постгипоксический период в нейронах злкПВЯ сохранялись основные показатели вазопрессин-синтезирующей и нейросекреторной активности. Установлена высокая реактивность медиального мелкоклеточного субъядра ПВЯ (мкПВЯ) на ГГ в виде гипертрофии нейронов, роста концентрации РНК, увеличения иммунореактивности к вазопрессину с повышением его концентрации. ГГ приводили к повышению иммунореактивности к белкам cFos, HIF-1α и HIF-3α в ммПВЯ. В постгипоксический период в ммПВЯ происходило уменьшение иммунореактивности к вазопрессину и снижение его содержания. Реакция СОЯ на ГГ характеризовалась развитием дистрофических изменений в нейроцитах и органеллах,сопровождалась снижением концентрации РНК в нейронах, уменьшением иммунореактивности к белкам HIF-1α, HIF-3α, cFos и к вазопрессину. В течение постгипоксического периода отмечалось частичное восстановление морфофункционального состояния нейронов СОЯ. The dissertation presents a theoretical justification and an experimental solution to an urgent scientific problem, which is to establish the mechanisms of the vasopressinergic system of the hypothalamus participation in the neuroendocrine response of the brain to the long term intermittent hypobaric hypoxic hypoxia and to study the features of the morphofunctional state of vasopressinergic neurons in the posthypoxic period. Based on quantitative immunohistochemical and immunofluorescence studies of serial sections of the hypothalamus, it was shown that the long term intermittent hypoxic hypoxia led to hypertrophy of the neurons of the lateral subdivision of the posterior magnocellular subnucleus of the paraventricular hypothalamic nucleus (PVNpml) with an increase in the area of the cytoplasm and nucleoli, as well as accumulation of cytoplasmic RNA. The increase of vasopressin concentration was noted in the magnocellular neurons and their axons, which led to a significant increase in the vasopressin total content in the PVNpml. Hypoxia resulted in an increase in immunoreactivity to cFos, HIF-1α, and HIF-3α proteins in the PVNpml in combination with an increase of these proteins’ concentration in neurocytes and an increase in the total content of these proteins within the subnuclei. An increase in the functional activity of neurons of the PVNpml with an increase of vasopressin synthesis and secretion in response to hypoxic stimulation was combined with an increase in the concentration of mRNA for the HIF-1α and HIF-3α proteins in the mediobasal hypothalamus. It is noteworthy that 10 days after the end of hypoxic conditions, signs of neurons hypertrophy were present in the PVNpml while RNA concentration increased in the nucleoli of neurocytes, and the main parameters of the neurosecretory activity of magnocellular neurons remained higher compared with the control parameters that indicated the prolongation of high functional activity of magnocellular vasopressinergic neurons in the posthypoxic period. Thus, the nature of PVNpml neurons functional activity alteration in response to hypoxia and in the posthypoxic period indicates the involvement of magnocellular vasopressinergic neurons in the processes of neuroendocrine adaptation to hypoxia. The study of the morphofunctional state of the medial pavocellular subnuclei of the paraventricular hypothalamic nucleus (PVNmp) demonstrated a high reactivity of neurosecretory cells to the 15 day hypoxic stimulation. Morphometric analysis showed that hypoxic influence result in the hypertrophy of neurons and an increase in the area of the cytoplasm with the increase in RNA concentration. The area of vasopressin immunoreactivity in the cytoplasm of neurons its concentration and total content in the subnuclei increased, that testified an increase in the synthesis of neuropeptide under the influence of hypoxia. A similar increase in immunoreactivity and vasopressin content was observed in neuronal axons in the region of the PVNmp, which indicated that intermittent hypoxic hypoxia stimulated neurosecretion processes. The immunoreactivity to cFos, HIF-1α and HIF-3α proteins increased under the influence of hypoxia in the PVNmp, that was accompanied with an increase in their content in the structure and an increase in their concentration in the mediobasal hypothalamus. It is characteristic that in the posthypoxic period, signs of neurons’ hypertrophy in the PVNmp not only remained, but continued to increase. At the same time, a decrease in the immunoreactivity to vasopressin and its content both in the neurons and in the axons was observed in the structure, which indicated a decrease in the synthesis and neurosecretion processes in the vasopressinergic neurons of the PVNmp in the posthypoxic period. At the same time, the cFos protein content in the structure decreased to the control level while HIF family proteins content in neurocytes maintained increased. Therefore, the peculiarities of PVN neurons reaction to the long term intermittent hypoxic hypoxia, apparently, evidence the involvement of the vasopressinergic system in the mechanisms of the integral neurosecretory response to hypoxia with the formation of a systemic structural trace of adaptation. A different reaction to the long term intermittent hypoxic hypoxia was demonstrated by magnocellular neurons of the supraoptic nucleus of the hypothalamus (SON), in which dystrophic changes were observed in neurocytes and their organelles in combination with a decrease in RNA concentration. The magnocellular supraoptic neurons reacted to hypoxia by a decrease in immunoreactivity in the HIF-1α and HIF-3α marker proteins; no significant change in the content of these proteins in neurocytes was observed. At the same time, the immunoreactivity to the cFos protein of the early neurosecretory response significantly decreased in the SON, the concentration of protein in neurons and its total content in the SON decreased. The neurosecretory response of magnocellular supraoptic neurons to hypoxia was characterized by a limitation of vasopressin immunoreactivity in neurons, a decrease in the hormone concentration in neurocytes and its total content in the SON, which indicated a reduction of vasopressin biosynthesis in magnocellular supraoptic neurons. At the same time, in the axons of neurons in the supraoptic region, hypoxia increased the immunoreactivity and the total vasopressin content, which indicated an acceleration of neurohormone’s neurosecretion processes. At the end of the 10-day posthypoxic period, a partial reduction of dystrophic changes in the neurons of the SON was observed while decreased level of RNA in the neurocytes remained. The parameters of vasopressin immunoreactivity and the neurohormone content were almost completely restored in neurocytes and in the axons of the SON neurons, expression of the cFos protein and immunoreactivity to HIF-1α and HIF-3α proteins were partially restored. Thus, the long term intermittent hypoxic hypoxia exposure caused the inhibition of vasopressin synthesis in neurons of the SON with a moderate acceleration of neurosecretion processes. At the same time, during the posthypoxic period, there is a steady tendency to restore the morphologic and histochemical characteristics and neurosecretory function of supraoptic neurons, however, the 10-day posthypoxic period is insufficient to restore the functional activity of the SON completely.
Функциональное состояние вазопрессинергической системы гипоталамуса при действии прерывистой гипоксической гипоксии
The Functional State of the Vasopressinergic System of the Hypothalamus After Intermittent Hypoxic Hypoxia Influence
Keywords: переривчаста гіпоксична гіпоксія; вазопресин; білок cFos; фактори HIF-1α та HIF-3α, індуковані гіпоксією; паравентрикулярне ядро гіпоталамуса; супраоптичне ядро гіпоталамуса; прерывистая гипоксическая гипоксия; вазопрессин; белок cFos; факторы HIF-1α и HIF-3α, индуцибельные гипоксией; паравентрикулярное ядро гипоталамуса; супраоптическое ядро гипоталамуса; intermittent hypoxic hypoxia; arginine vasopressin; cFos protein; hypoxia inducible factors HIF-1α and HIF-3α; paraventricular nucleus of the hypothalamus; supraoptic nucleus of the hypothalamus